Impact of contact force on the lesion characteristics of very high‐power short‐duration ablation using a QDOT‐MICRO catheter - Junji Yamaguchi; Masateru Takigawa; Masahiko Goya; Claire A. Martin; Miho Negishi; Tasuku Yamamoto; Takashi Ikenouchi; Kentaro Goto; Takatoshi Shigeta; Iwanari Kawamura; Takuro Nishimura; Tomomasa Takamiya; et al. (Journal of Arrhythmia, 2024)
Abstract Background Lesion size is reported to become larger as contact force (CF) increases. However, this has not been systematically evaluated in temperature‐guided very high‐power short‐duration (vHPSD) ablation, which was therefore the purpose of this study. Methods Radiofrequency applications (90 W/4 s, temperature‐control mode) were performed in excised porcine myocardium with four different CFs of 5, 15, 25, and 35 g using QDOT‐MICRO™ catheter. Ten lesions for each combination of settings were created, and lesion metrics and steam‐pops were compared. Results A total of 320 lesions were analyzed. Lesion depth, surface area, and volume were smallest for CF of 5 g than for 15, 25, and 35 g (depth: 2.7 mm vs. 2.9 mm, 3.0 mm, 3.15 mm, p < .01; surface area: 38.4 mm2 vs. 41.8 mm2, 43.3 mm2, 41.5 mm2, p < .05; volume: 98.2 mm3 vs. 133.3 mm3, 129.4 mm3, 126.8 mm3, p < .01 for all pairs of groups compared to CF = 5 g). However, no significant differences were observed between CFs of 15–35 g. Average power was highest for CF of 5 g, followed by 15, 25, and 35 g (83.2 W vs. 82.1 W vs. 77.1 W vs. 66.1 W, p < .01 for all pairs), reflecting the higher incidence of temperature‐guided power titration with greater CFs (5 g:8.8% vs. 15 g:52.5% vs. 25 g:77.5% vs. 35 g:91.2%, p < .01 for all pairs except for 25 g vs. 35 g). The incidence of steam‐pops did not significantly differ between four groups (5 g:3.8% vs. 15 g:10% vs. 25 g:6.2% vs. 35 g:2.5%, not significant for all pairs). Conclusions For vHPSD ablation, lesion size does not become large once the CF reaches 15 g, and the risk of steam‐pops may be mitigated through power titration even in high CFs.